THE “DEFERENCE” OF JUDICIAL AUTHORITY TO THE STATE* - Nomthandazo Ntlama (Obiter, 2021)
The adoption of the Constitution of the Republic of South Africa, 1996 (hereinafter “the Constitution”), provided an opportune moment for the courts, especially the Constitutional Court to ensure an appropriate balance in the development of the principles and values of the doctrine of separation of powers vis-à-vis those of judicial review. The Constitution is framed in a manner that entrenches a system of checks and balances (this is deduced from the manner in which the various chapters of the Constitution are structured, dealing with the roles of the legislature, executive and the judiciary). This system gives the general public a legislative and executive authority that is accountable to them subject to judicial review by an independent judiciary. The system of checks and balances affirms the limited power of the legislative and executive authorities which is confined within the constraints of constitutional values and principles. The importance of checks and balances is similarly endorsed by Edwards as a system that has ushered in a new process of the regulation of state authority in the new dawn of democracy. This system envisages a move away from a culture of authority of the apartheid rule to one of justification of the new constitutional dispensation. He substantiates his argument by pointing out that the new process of regulating state authority has enabled the courts to educate other branches of government through principled and robust articulations of the foundational and constitutional values of the Constitution in a democratic society. Against this background, the purpose of this note is to provide a brief overview of the Merafong Demarcation Forum v President of the Republic of South Africa (2008 (10) BCLR 968, hereinafter “Merafong”) judgment. The particular emphasis on this judgment is its potential to defer the judicial authority (which the author refer to as a “political doctrine”) to the state. The objective is to analyse this doctrine and evaluate it against the development of substantive principles of judicial review. This purpose is motivated by Chaskalson CJ’s argument in Pharmaceutical Manufacturers Association of South Africa: In re Ex Parte President of the Republic of South Africa (2000 (3) BCLR 241). Chaskalson CJ in this case held that the Constitutional Court cannot allow itself to be diverted from its main function as the final and independent arbiter in the contest between the state and its citizens. In Merafong, the court created an impression of having misconstrued this purpose and the objectives it has to fulfil. This note is limited to the “political approach” which the court emphasised without much thought, and attempt to address the question of public involvement in legislative processes raised in this case. It also acknowledges that the court has affirmed its independence as the guardian of the Constitution in the regulation of state authority and advancement of the principles of judicial review, but its lack of consistency in its adopted approach is a worrying factor and a cause for concern for the regulation of state authority.